Dampak La Nina 2021-2022 terhadap Peningkatan Curah Hujan - Wandi Nusa Harahap; Betti Yuniasih; Sri Gunawan (Program Studi Agroteknologi INSTIPER, 2023)
La Nina is a climate anomaly that can cause extreme weather. La Nina is marked by a decrease in the sea surface temperature of the Pacific Ocean at the equator. La Nina can cause a prolonged rainy season for Asia including Indonesia. From mid-2020 to the end of 2022, Indonesia has experienced La Nina events. This study aims to determine changes in rainfall patterns and the number of rainy days during La Nina events. This research was conducted descriptively, using Pacific Ocean sea surface temperature (SST) data and rain data originating from the BMKG Climatology Station of Sultan Syarif Kasim II Pekanbaru from data for the last 10 years 2013-2022. The results of the study show that La Nina occurred from October 2020 to December 2022 with a weak to moderate level of La Nina strength. La Nina has increased the amount of rainfall 54-90% from normal conditions and increased the number of rainy days 11-70% compared to climate with normal conditions. Monthly rainfall is in the low to high category, while daily rainfall is included in the heavy rain category. The La Nina event has caused a prolonged rainy season for almost 3 years and has increased the amount of rainfall and rainy days.